The Impact Of Digital Communication Via The Internet On Social Relations Between Family Members In Algerian Society (A Field Study On A Sample Of University Youth In The City Of Khenchela - Algeria) (Journal of Namibian Studies : History Politics Culture, 2024)
This study falls within the framework of sociological research on social communication and family relationships, and aims to reveal the impact that digital communication through new communication media can have on family dynamics and relationships between its members. This research seeks to highlight the characteristics of this new form of communication, represented by digital communication, which has repositioned elements of traditional communication processes through the use of multimedia. The aim is to identify the psychological and social effects that this type of communication has on the family. The importance of this study lies in the emergence of modern electronic means of social communication, which have brought about changes in the family relationships between family members, their forms of interaction and their methods of communication. Since the current study is about the effects of digital communication on family relationships, it is classified as descriptive research, which aims to describe the nature and characteristics of the population studied.